The design and rationale of SAVE BC: The Study to Avoid CardioVascular Events in British Columbia. Issue 7 (11th June 2018) - Brunham, Liam R.; Lynch, Kelsey; English, Amy; Sutherland, Rory; Weng, Jian; Cho, Raymond; Wong, Graham C.; Anis, Aslam H.; Francis, Gordon A.; Khan, Nadia A.; McManus, Bruce; Wood, David; et al.
Abstract : Atherosclerotic cardiovascular disease (ASCVD) is highly heritable, particularly when it occurs at a young age. The screening of individuals with premature ASCVD, although often recommended, is not routinely performed. Strategies to address this gap in care are essential. We designed the Study to Avoid CardioVascular Events in British Columbia (SAVE BC) as a prospective, observational study of individuals with a new diagnosis of very premature ASCVD (defined as age ≤ 50 years in males and age ≤ 55 years in females) and their first‐degree relatives (FDRs) and spouses. FDRs and spouses will undergo screening for cardiovascular (CV) risk factors and subclinical ASCVD using a structured screening algorithm. All subjects will be followed longitudinally for ≥10 years. The overall goal of SAVE BC is to evaluate the yield of a structured screening program for identifying individuals at risk of premature ASCVD. The primary objectives of SAVE BC are to identify and follow index cases with very premature ASCVD and their FDRs and to determine the diagnostic yield of a structured screening program for these individuals. We will collect data on CV risk factors, medication use, CV events, and healthcare costs in these individuals. SAVE BC will provide insight regarding approaches to identify individuals at risk for premature ASCVD with implications for prevention and treatment in this population.